Eating Habits of 7-12 Year-Old Children in Tabriz, Iran - Cakiroglu, F. Pinar; Malek, Mahsa (Pakistan Journal of Nutrition, 2007)
This study aimed to identify the eating habits of second and fifth graders from Tabriz, Iran. A total of 160 pupils were selected through random sampling at Sehit Sobhani Elementary School in the Kutb district of Tabriz. The sample consisted of 80 girls and 80 boys; 83 second graders and 78 fifth graders. Pupils` BMI measures showed that 52.4% of the second graders and 46.2% of the fifth graders had normal physical structure. The results further suggested that the percentage of pupils who ate three meals per day was 60.6%. The most commonly skipped meal was breakfast (55.6%) and those who did have breakfast mostly preferred cheese and tea. Most pupils preferred meat dishes to vegetable dishes. It was thus concluded that pupils needed to be informed about the importance of breakfast and the requirements of a healthy diet.